Dimensions of energy insecurity on small islands: The case of the Maldives - Mohamed Shumais; Ibrahim Mohamed (Asian Development Bank Institute (ADBI), 2019)
The study explores the dimensions of energy insecurity on small islands in terms of heavy dependence on fossil fuels and the challenges involved in improving efficiency and renewable energy capacity to enhance energy security in the electricity system. Although all inhabited islands in the Maldives have made progress in electrification, the goal of achieving a secure, reliable supply of energy while changing to a low-carbon energy system has been challenging. However, every country faces a distinctive energy security outlook. Although the Maldives is the first and only country in South Asia with 100% access to electricity, the geographic spread necessitates the electrification of each island with its own diesel-powered mini-grid system, resulting in an expensive and inconsistent supply. The power sector continues to depend on fossil fuels, although the transformation to renewable energy has begun, particularly through solar photovoltaic hybrid systems. An evaluation in the context of the targets of SDG 7 for the Maldives offers insights into the distinctive energy security issues that small islands face, suggesting how they could develop their policies and priorities.
Keywords: Q01; Q42; Q48; Q56; L94; 330; small island developing states; Maldives; energy insecurity; renewable energy; electricity; sustainable development goals